Beyond Pain Scales: A Critical Phenomenology of the Expression of Pain - Miglio, Nicole; Stanier, Jessica (Frontiers in Pain Research, 2022)
In this paper, we discuss the qualitative dimension of painful experiences by exploring the role of imagination and metaphorical association in the conceptualization and expression of pain. We employ an engaged critical-phenomenological approach to offer original analysis influenced by the perspectives of people in pain. The paper is organized into three parts. Part 1 reviews literature on the expression of pain, its communication, and its reception—attending in particular to the emphasis on verbalizing pain in healthcare contexts. We here discuss benefits and limitations of standard methods aimed at facilitating the meaningful expression of pain (such as “pain scales”) from the perspectives of patients and practitioners, respectively. We suggest that these methods might be importantly complemented by facilitating creative expression of painful lived experiences with respect to personal lifeworlds. Part 2 deals with the role of imagination and metaphorical association in making sense of pain. We explore how imagination is a cognitive and affective mode of experiencing the world which plays a crucial role in determining how pain is experienced, as well as helping to make sense of pain figuratively in relation to the lifeworld. In Part 3, we draw from principles of engaged phenomenology to foreground case studies in which projects have been able facilitate the intersubjective expression of pain. These examples demonstrate the value of attending to the contours of painful lifeworlds in their specificity, affording both agency and accessibility in their communication, while remaining mindful of the complex power relations which govern perceived legitimacy and testimony relating to the transformation of pain. The overall paper aims to contribute to literature on qualitative pain research on both theoretical and practical levels. By exploring the expression of pain through phenomenology, we aim to enrich current debate on the qualitative experience of pain. We also seek to critically highlight the socio-political dimensions which frame painful experiences, their expression, their lived significance, and their treatment.